Fracture in Ceramic Materials and their Toughening - ชนะดี ธวัช (KKU Science Journal, 2016)
This review article presented an understanding of brittle ceramic materials. The main topics including typical properties, fracture mechanic and toughening of ceramic materials were proposed. Toughening arose from the ability of materials to absorb energy and plastically deform before being fractured by different mechanisms such as crack deflection, transformation toughening, microcracking and fiber pull-out through particulate or fiber reinforcement in ceramic matrix. This information can be used for guiding the processing design to increase the strength of ceramic materials.